Winter sports injuries in elite female athletes: A narrative review - Rotllan, C.; Viscor, G. (International Journal of Environmental Research and Public Health, 2024)
There is a lack of reviews covering the topic of the parallel high prevalence of injuries in female winter sport elite athletes. We aimed to review the data on incidence and patterns of injuries in female athletes participating in official competitions of winter sports. We conducted a comprehensive literature search on epidemiological data and etiological information on alpine skiing, snowboarding, ski jumping and cross-country skiing. The most common location of injury was the knee among skiers and ski jumpers and the incidence of severe ACL events was 7.6 per 100 ski racers per season (95% CI 6.6 to 8.9) in female alpine skiers. Snowboarders and cross-country skiers were more affected in the ankle and the foot. The most common cause was contact trauma with stagnant objects. The injury risk factors include training volume, knee pre-injuries, the period of the season and the technical equipment. Females are at greater risk of suffering from overuse injuries during the competitive season, as opposed to male athletes who are more likely to suffer from traumatic injuries. Our findings can be used to inform coaches and athletes and to guide future injury prevention plans.